Mediterranean radiocarbon offsets and calendar dates for prehistory - Manning, Sturt W.; Kromer, Bernd; Cremaschi, Mauro; Dee, Michael W.; Friedrich, Ronny; Griggs, Carol; Hadden, Carla S. (Science advances, 2020)
A single Northern Hemisphere calibration curve has formed the basis of radiocarbon dating in Europe and the Mediterranean for five decades, setting the time frame for prehistory. However, as measurement precision increases, there is mounting evidence for some small but substantive regional (partly growing season) offsets in same-year radiocarbon levels. Controlling for interlaboratory variation, we compare radiocarbon data from Europe and the Mediterranean in the second to earlier first millennia BCE. Consistent with recent findings in the second millennium CE, these data suggest that some small, but critical, periods of variation for Mediterranean radiocarbon levels exist, especially associated with major reversals or plateaus in the atmospheric radiocarbon record. At high precision, these variations potentially affect calendar dates for prehistory by up to a few decades, including, for example, Egyptian history and the much-debated Thera/Santorini volcanic eruption. - Intra-annual offsets in Northern Hemisphere atmospheric radiocarbon levels challenge and complicate Old World radiocarbon dating. - Intra-annual offsets in Northern Hemisphere atmospheric radiocarbon levels challenge and complicate Old World radiocarbon dating.